1988
DOI: 10.1002/gps.930030105
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorder among nursing home patients: Preliminary findings from the national nursing home survey pretest

Abstract: Ninety‐six per cent of mentally ill elderly persons who are not in the community reside in nursing homes, yet the mental health care they receive here is minimal or unavailable. Data are presented from the 1984 pretest of the National Nursing Home Survey. Five hundred and twenty‐six patients in 112 nursing homes in four US metropolitan areas were sampled. Overall, the prevalence of mental disorder was found to be 68%; 39% of the patients had a diagnosis of organic brain syndrome (OBS) and 29% had other mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

1989
1989
1998
1998

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(26 citation statements)
references
References 12 publications
2
23
1
Order By: Relevance
“…Both shortly after admission and 6 months later, neuroleptics are the most frequently taken drug classes, which is in accordance with the data of authors using a point-prevalence design (e.g. Mann et al 1984Mann et al , 1986Burns et al 1988;Beardsly et al 1989). To our knowledge, no authors investigating psychotropic drug intake shortly after admission have compared different types of psychotropics.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Both shortly after admission and 6 months later, neuroleptics are the most frequently taken drug classes, which is in accordance with the data of authors using a point-prevalence design (e.g. Mann et al 1984Mann et al , 1986Burns et al 1988;Beardsly et al 1989). To our knowledge, no authors investigating psychotropic drug intake shortly after admission have compared different types of psychotropics.…”
Section: Discussionsupporting
confidence: 71%
“…Kalchthaler et al 1977;Segal et al 1979;Ray et al 1980;Clarke et al 1981;Beers et al 1988;Buck 1988;Burns et al 1988;Beardsly et al 1989). The rates of psychotropic drug intake reported from these studies lie between 32 % (Burns et al 1988) and 86% (Segal et al 1979). Of the different types of psychotropic drugs, most studies indicated that neuroleptics or hypnotics were used most frequently, while the use of antidepressants and anxiolytics was less common.…”
Section: Introductionmentioning
confidence: 94%
“…An association between decline in brain dopaminergic activity with age and cognitive and motor impairment has been shown in healthy volunteers (Volkow et al, 1998) The elderly The elderly are becoming an increasingly important group at risk of depression. It has been estimated that up to 18% of elderly people in the community have symptomatic depression (Evans et al, 1991;Raskind, 1992), whilst the incidence among geriatric patients in nursing homes and those with chronic diseases may be substantially higher (Burns et al, 1988). However, depression in the elderly frequently goes undiagnosed because many patients and their families mistake it to be part of the normal aging process.…”
Section: Cognitive Dysfunctionmentioning
confidence: 97%
“…More recently, the 1985 National Nursing Home Survey (National Center for Health Statistics, 1989) and the earlier NNHS pretest (Burns et al, 1988) found that 63% of residents had a dementing illness. These surveys, however, relied on reviews of nursing records and interviews with nursing staff conducted by non-clinicians.…”
Section: Epidemiologymentioning
confidence: 98%